The Practical Manifestation of the Dangers of Online Space Through A Generational Lens - Berényi , Csaba; Csiszárik-Kocsir, Ágnes; Varga, János (Journal of Ecohumanism, 2025)
Today’s accelerating pace of digitalisation will require new skills and competences for all economic actors. Operating in the online space has many risks in addition to its advantages over the physical space. It is therefore essential that we equip ourselves with the knowledge to be able to identify and filter these risks and threats in order to succeed in the digital world. The youngest age group is the most exposed to these risks, mainly the young people of generation Z and alpha. They are the ones who spend most of their time in the online space on various social media platforms and platforms. This substitution of online space for physical space has introduced new concepts such as cyberbullying, or cyberbullying. Freedom of expression, which is the main attraction of these platforms, can cause a lot of damage to the lives and self-esteem of individuals, but especially young people. Everyone who lives and works in the online space needs to be educated about these effects and how to protect themselves against them. The verbal abuse, defamation and harassment that we often experience can sometimes reach a level that needs to be addressed. The aim of our study is to examine the views and experiences of different generations in relation to exclusion, humiliation or abuse in the online space and their basic attitudes towards dealing with these situations. Based on the results of the primary research presented in this study, we want to give direction to the educational system or even to awareness-raising campaigns carried out by non-profit organisations, as to which age group or generation should be prepared for similar situations, showing them effective and appropriate solutions.